Empowering Elementary School Teachers As an Effort to Improve Pedagogical Competence Through a Program of Making Teaching Modules Based on Local Wisdom in Siak - Erlisnawati, Erlisnawati; Marhadi, Hendri; Alpusari, Mahmud; Fendrik, Muhammad; Vai, Aref; Risma, Devi (Journal of Community Engagement Research for Sustainability, 2025)
Teachers have a wide opportunity to develop teaching modules according to their needs, student characteristics and regional characteristics.  However, the reality in the field has not fully run as it should. It can be seen from the teaching modules used that there is no connection with local wisdom found in the area where education is carried out. For this reason, a training is needed through teacher empowerment, especially elementary school teachers in Siak Regency who have high potential to be able to develop teaching modules based on local wisdom. This service program aims to improve teachers' pedagogical competence in making teaching modules based on local wisdom in Siak. The service was carried out to teachers of SDN 004 Buatan II, Koto Gasib District, Siak Regency, Riau Province. The method used in this service is the participatory method, which involves the community as a subject in development. Empowerment activities are carried out in the form of face-to-face workshops (offline).